Periodical Medical Examination of Elderly Population in Moscow - E. V. Zemlyanova; A. A. Savina; A. M. Podchernina (Здоровье мегаполиса)
Background. Senior citizens’ health, healthy aging, and active longevity have become at the top of the agenda while life expectancy is increasing. These issues are among the priorities for Moscow, as a metropolis with high levels of life expectancy in elderly age groups. Preventive healthcare is crucial to ensuring a good level of health and post-retirement activity among the older population.Objective. To evaluate the preventive activity of seniors, i.e., undergoing periodical medical examination, in Moscow compared to the Russian Federation as a whole.Materials and methods. The authors used the microdata sets from the study of the population’s health status conducted by the Federal State Statistics Service of the Russian Federation (ROSSTAT) using the representative sampling method in 2023.Results. The commitment of elderly people to make regular health check-ups also depends on the behavioral risk factors. Respondents without a smoking habit, including non-smokers, former smokers, and those who have never smoked, take the most care of their own health: 60.3% and 63.8% of them underwent periodical medical examinations in Russia and Moscow, respectively.Discussion. The elderly population shows insufficient activity in undergoing free periodical medical examinations. People aged 60-74 years are most committed to this type of preventive measure. Women take more care of their own health. The level of respondents’ responsibility for their own health increases with the level of respondents’ education.